Factors Related to the Implementation of the One House One Larvae Monitoring Movement for the Prevention of Dengue Hemorrhagic Fever - Yana Riana; Dewi Rahayu; Aila Karyus; Endang Budiati; Dian Utama Pratiwi Putri (Knowledge Dynamics, 2025)
Background: Prevention efforts through the One House One Larvae Monitoring, which is a government program in Indonesia to monitor and control the spread of dengue fever (DBD). The movement has not been running optimally, as indicated by the increasing number of cases year by year. Several factors, such as knowledge, attitude, the role of health workers, and the presence of mosquito larvae monitor cadres, are suspected to influence the implementation of this movement. This study aims to identify the factors associated with the implementation of the One House One Larvae Monitoring Movement activities for dengue fever prevention in Pesisir Barat Regency, Indonesia in 2025. Methods: This study is a quantitative, cross-sectional study, employing a simple random sampling technique. The research subjects were heads of households while the study variables included knowledge, attitude, the role of health workers, mosquito larvae monitor cadres, and the implementation of One House One Larvae Monitoring. The research was conducted from March 4 to March 25, 2025. Data analysis was performed using multiple logistic regression. Results: The results of the study indicate a significant relationship between knowledge (p = 0.000), attitude (p = 0.000), the role of health workers (p = 0.005), and mosquito larvae monitor cadres or Jumantik cadre (p = 0.007) with the implementation of One House One Larvae Monitoring. The dominant factor influencing the implementation of this movement is knowledge, with an Exp(B) value of 6.986. Conclusions: It is recommended that the local government and health workers be more active in conducting socialization and empowering mosquito larvae monitor cadres, as well as encouraging active community involvement in the implementation of the One House One Larvae Monitor Movement as a sustainable effort to prevent dengue fever.